Pengaruh Kepercayaan Pada Keterlibatan Nasabah Di PT.Axa Mandiri - Wisnu Syahputra, Noval (Jurnal Syntax Fusion, 2025)
This study aims to analyze the influence of trust on customer engagement and its impact on customer loyalty at PT. AXA Mandiri Tangerang Selatan, with service quality as a mediating variable. The insurance industry faces challenges in building long-term relationships with customers, making understanding the factors that influence loyalty crucial. This research employs a quantitative method using path analysis technique. The research sample consists of 140 respondents who are customers of PT. AXA Mandiri, aged at least 18 years, selected through purposive sampling. Data were collected using an online questionnaire with a Likert scale of 1-4. The variables studied include trust (8 indicators), customer engagement (8 indicators), service quality (6 indicators), and customer loyalty (6 indicators). The results show that trust has a positive and significant effect on customer engagement (β=0.721; p<0.05). Customer engagement has a positive effect on service quality (β=0.520; p<0.05) and customer loyalty (β=0.256; p<0.05). Trust and service quality also have direct effects on customer loyalty with coefficients of 0.206 and 0.354, respectively. Mediation analysis reveals that customer engagement mediates the relationship between trust and customer loyalty. These findings imply the importance of building customer trust through quality service to enhance engagement and loyalty at PT. AXA Mandiri.